Resection of Nonalcoholic Steatohepatitis-Associated Hepatocellular Carcinoma: A Western Experience. (2nd September 2012) - Shrager, Brian; Jibara, Ghalib A.; Tabrizian, Parissa; Roayaie, Sasan; Ward, Stephen C.
Abstract : Introduction . Hepatocellular carcinoma is now known to arise in association with nonalcoholic steatohepatitis. The aim of this study is to examine the clinicopathological features of this entity using liver resection cases at a large Western center. Methods . We retrospectively reviewed all cases of partial liver resection for hepatocellular carcinoma over a 10-year period. We included for the purpose of this study patients with histological evidence of nonalcoholic steatohepatitis and excluded patients with other chronic liver diseases such as viral hepatitis and alcoholic liver disease. Results . We identified 9 cases in which malignancy developed against a parenchymal background of histologically-active nonalcoholic steatohepatitis. The median age at diagnosis was 58 (52–82) years, and 8 of the patients were male. Median body mass index was 30.2 (22.7–39.4) kg/m 2 . Hypertension was present in 77.8% of the patients and diabetes mellitus, obesity, and hyperlipidemia in 66.7%, respectively. The background liver parenchyma was noncirrhotic in 44% of the cases. Average tumor diameter was7.0 ± 4.8  cm. Three-fourths of the patients developed recurrence within two years of resection, and 5-year survival was 44%. Conclusion . Hepatocellular carcinoma may arise in the context of nonalcoholic steatohepatitis, often before cirrhosis has developed. Locally advanced tumors are typical, and long-term failure rate following resection is high.